Physical, structural, elastic and optical properties of neodymium oxide doped zinc tellurite glass system with silver incorporation - Awshah, Abdulbaset A. Abdulla (2019)
Four series of zinc tellurite glasses doped with neodymium oxide and neodymium oxide nanoparticles with chemical composition equations [(TeO2)0.7(ZnO)0.3](1- x)(Nd2O3)(x) (TZN) , [(TeO2)0.7(ZnO)0.3](1- x)(Nd2O3NPs)(x)(TZNnPs),{[(TeO2)0.7(ZnO)0.3](1-x)(Nd2O3)(x)}(0.99) (Ag2O)(0.01) (TZAN), {[(TeO2)0.7 (ZnO)0.3](1-x) (Nd2O3 NPs) (x)}(0.99) (Ag2O)0.01 (TZANnPs) have been prepared using the melt-quenching method. The aim of the work was to study the physical, structural, elastic and optical properties of the glasses with the view of achieving an improved application potential for the glasses. The choice of the glass composition was for high refractive index, easy glass formation as well as excellent absorption/emission in the infrared region. Density and molar volume measurement, X-ray diffraction (XRD), Fourier transform infrared (FTIR) and Transmission electron microscopy (TEM) were employed for these studies. Over the last few decades, the study of tellurite glasses and their applications in the areas of scientific, technological and industrial applications have been given a great deal of attention by glass scientists and technologists. Since TeO2 alone does not form glass, it must be combined with one or more another oxide to form a glass. Structural, optical, electrical and elastic properties of tellurium oxide-based glasses have been and are still under study. The XRD analyses patterns of all the four glass series showed a broad hump around 20-30o, confirming the glassy and amorphous nature of the glasses. The FTIR spectral analysis and the deconvolution of the spectra showed the presence and concentration of TeO3 and TeO4 structural units against the Nd2O3 molar concentration. The TeO4 concentration variation with Nd2O3 was used as the determinant of the variations in bridging and non-bridging oxygen concentrations. Density for all the series of glasses studied showed an increasing pattern from 5346 to 5580, 5346 to 5580, 5345 to 5954, 5410 to 5580 kg cm-3 with increase in Nd2O3/Nd2O3 NPs concentration in TZN, TZNnPs, TZAN and TZANnPs respectively. The TEM morphological structures for the two Nd2O3 NPs doped series revealed the NPs were agglomerated in the glass structure. The ultrasonic velocities and the elastic moduli for the glasses showed different patterns of non-linear variations against both the Nd2O3 micro particles and nanoparticles. Other elastic parameters studied include the microhardness, Poisson’s ratio, softening temperature, Debye temperature, fractal bond connectivity and fugacity. Theoretical data sets for the elastic properties of the glass systems were obtained using the Makishima and Mackenzie model, Rocherulle model, bond compression and ring deformation models. The values obtained for the elastic moduli using the Makishima and Mackenzie model and Rocherulle model are in excellent agreement with the corresponding experimental set of data. The bond compression model set of data for all the four series of glasses studied presented much higher values of the elastic moduli when compared with the corresponding experimental values of the elastic moduli and thus the model is not suitable for these systems of glasses. The UV-Vis spectra for all the glass series showed cut-off wavelengths that are not sharp (showing amorphous nature), with absorptions peaks due to Nd3+ ions around 435, 460, 478.5, 507.5, 530, 601.5, 635, 685.5 and 752.5 nm wavelengths, corresponding to transitions from 4I9/2 to 2P1/2, 4I9/2 to 4G11/2, 4I9/2 to (2K15/2 + 2G9/2 + 2D3/2), 4I9/2 to 4G9/2, 4I9/2 to (4G7/2+4G9/2), 4I9/2 to (4G5/2+2G7/2), 4I9/2 to 2H11/2, 4I9/2 to F9/2, 4I9/2 to (4F7/2+4S3/2) respectively. The optical energy band gaps in all the glass series showed non-linear relationships against the Nd2O3 concentration showing a clear dependence on the TeO4 concentration. The refractive index value ranges for TZN, TZNnPs, TZAN and TZANnPs glass systems are 2.5331 - 2.6371, 2.54695 - 2.60927, 2.5440 - 2.6184 and 2.5567 - 2.6240 respectively. High refractive index values (Higher than conventional silicate/phosphate/other glasses currently in use), polarizability, optical basicity as well as favorable metallization criterion values (0.3 < M < 0.45) suggests the glasses have good potential for application in areas of the laser and nonlinear optical applications. Other optical parameters studied include the reflection loss, transmission coefficient, dielectric constant and the polaron radius. The values of the refractive index, metallization criterion, optical basicity, dielectric constant and polarizability showed that the glasses studied can be used for optical fiber and laser applications. Considering their high refractive indices, all the four series have shown advantage against other glasses conventionally used in the fiber and amplifier technology such as tellurite (2.0 - 2.3) , silicate (1.5 - 1.8), , sulfide (around 2.2) and Phosphate (around 1.65) glasses. Putting their elastic (Elastic Moduli, Microhardness, Softening temperature) and optical properties (UV-Vis intensity/effective bandwidth, refractive index, metallization criterion, optical basicity, transmission coefficient) together into consideration, the TZANnPs glass system appeared to have more overall advantage over the other three glass systems for application in both photonics and amplifier technology.